2018
DOI: 10.1177/0017896918793661
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting schools in Taiwan: School principals’ and teachers’ perspectives on implementation and sustainability

Abstract: Objective: This study assessed school principals’ understanding, attitudes and willingness to influence the implementation of the health-promoting schools (HPS) programme in Taiwan and teachers’ willingness to sustain it. Method: In 2014, a total of 1,140 school principals and 1,110 teachers (HPS coordinators) completed questionnaires concerning their perspectives on implementation and sustainability. Results: Compared with teachers, school principals reported higher levels of willingness to sustain HPS implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
3
14
0
5
Order By: Relevance
“…With regard to the school-leader-oriented influencing factors, our results confirm the findings of previous studies [19][20][21][22]. HPS attitudes and competencies served as significant predictors for HPS implementation for both male and female school leaders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to the school-leader-oriented influencing factors, our results confirm the findings of previous studies [19][20][21][22]. HPS attitudes and competencies served as significant predictors for HPS implementation for both male and female school leaders.…”
Section: Discussionsupporting
confidence: 89%
“…Evidence from the Norwegian Network on Health Promoting Schools suggests that a positive attitude of the school leader towards school health promotion was perceived as key for running the program at schools and for sustaining it over time [20,21]. Moreover, current research results from Taiwan with n = 1.140 school principals and n = 1.110 HPS coordinators (i.e., teachers) indicate that school leaders' understanding of the HPS and their willingness to sustain HPS at their school were significantly associated with higher levels of HPS implementation and teachers' willingness to implement HPS on a continuing basis [22]. With regard to prior evidence, it is surprising that there is neither standardized training nor any defined regulations for specific competencies on HPS implementation of school leaders in Germany.…”
Section: Introductionmentioning
confidence: 67%
“…Although only a single school case study, the results are consistent with previous research highlighting the importance of aligning HPS interventions with the core business of schools and having adequate internal and external resources available to progress implementation (Hoyle et al, 2008;Inchley et al, 2007). Support from school leadership, in particular the school principal, is important in creating a health-promoting environment because of the power and influence they possess (Liu et al, 2019;McIsaac et al, 2015;Viig et al, 2012). Other research has pointed to the importance of committed teachers, policy alignment and support from senior management in achieving success with an HPS approach (Larsen and Samdal, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Previous research has identified factors known to assist in the implementation of the HPS approach. These include, but are not limited to, following the framework to implement an HPS approach; drawing upon committed staff, school leadership and management, health agencies and local HPS experts; establishing professional HPS networks; providing training and education in school health promotion; aligning HPS interventions with existing school policies and core business; and ensuring adequate internal and external resources (Hoyle et al, 2008;Hung et al, 2014;Inchley et al, 2007;Liu et al, 2019;McIsaac et al, 2015;Stolp et al, 2015). State and national policy support for the HPS framework can also affect successful implementation (Deschesnes et al, 2010;Inchley et al, 2007;Lee at al., 2001;Parsons et al, 1996;Turunen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on healthy school has some focus. Several studies have examining the context of health promoting schools [12], investigating the strategies used by health promoters to implement such initiatives, examining the co-occurrence of health behaviors to determine associations with meeting physical activity recommendations, describing the resources with a health promoting school (HPS) program [13], assessing school principals' understanding, attitudes and willingness to influence the implementation of the health-promoting schools (HPS) program and teachers' willingness to sustain it [14]. Exploring the strengths, challenges and improvement strategy for health-promoting schools [9].…”
Section: Introductionmentioning
confidence: 99%